Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kedisiplinan Guru Di SMA Negeri 1 Wakorumba Selatan Kabupaten Muna - Eli Safitri Budu; Zulkifli Musthan; Samrin Samrin (Jurnal Ilmiah Iqra', 2023)
This study aims to examine and analyze the principal's leadership style towards teacher discipline at SMA Negeri 1 Wakorumba Selatan, Muna Regency. The problems studied in this study are how the principal’s leadership style is, how the teacher’s discipline is,  and whether there is any influenceof the principal’s leadership style on teacher discipline.This study used quantitative research conducted at SMA Negeri 1 Wakorumba Selatan, Muna Regency, for 3 months from April to June 2022. The sample for this research was 21 teachers. Data collection techniques include documentation and questionnaires. In analyzing the data, the writer uses descriptive analysis and inferential analysis.The results showed that the leadership style of the principal of SMA Negeri 1 Wakorumba Selatan was in the moderate category, namely 15 or 71,4%. Teacher discipline at SMA Negeri 1 Wakorumba Selatan is in the moderate category, namely 15 or 71,4%. There is a significant influence of the principal's leadership style on teacher discipline at SMA Negeri 1 Wakorumba Selatan, Muna Regency 72,93%. This can be seen from the calculation results obtained for a significant level of 5%. Because tcount = 7,149 > ttable = 1,729, it can be concluded that H0 is rejected and Ha is accepted